The Nigerian Narrative on Human Security as Legitimate Security Concern in the Global South - Nuhu, Mailabari Bitrus; Terwase, Isaac Terungwa; Sampson, Osevwe Enoh; Kuma, Lanem Law (Kashere Journal of Politics and International Relations, 2025)
It pays in all senses to consider humanitarian crisis as a contemporary security threat. Some scholars suggests that human security rethinks beyond classical understanding as non-war, expanding to address both intra and interstate causes of conflicts such as hunger, disease, crime, repression and personal crisis usually caused by decades of war especially in worst hit areas like sub–Saharan Africa. This paper therefore argues that it is not only appropriate but timely to designate international aid and humanitarianism as legitimate security concerns. To achieve coherence, this work adopted the critical theory as its theoretical framework in analysing insecurity and methodologically associating it with the concept of human security. As such the discussion is divided into four main parts beginning from introduction and then to considering two main elements of human security: freedom from want and human needs as well as freedom from fear and the role of international aid before concluding. The basis of the argument is that human security is indeed as relevant as the threats of war in centralising the meaning of security as insecurity no longer denotes a state centric phenomenon of war because it as well represents any threat to human existence.